The Influence of Online Customer Reviews, Price Perception, and Promotion on the Intention to Purchase Shoes on Tokopedia - Muhamad Choirul Aziz,; Endah Budiarti , (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This research aims to analyze and prove the influence of online customer reviews, price perceptions and promotions on interest in buying shoes on Tokopedia. This research uses primary data obtained from distributing questionnaires using Google Form with a total of 95 respondents who had bought shoes on the Tokopedia marketplace. Data were analyzed using multiple linear regression techniques using Statistical Package for the Social Sciences (SPSS). The research results show that online customer reviews, price perceptions and promotions have a significant effect on interest in buying shoes on Tokopedia.